Zebrafish as a Model for the Study of Human Myeloid Malignancies. (3rd May 2015) - Lu, Jeng-Wei; Hsieh, Meng-Shan; Liao, Heng-An; Yang, Yi-Ju; Ho, Yi-Jung; Lin, Liang-In
Abstract : Myeloid malignancies are heterogeneous disorders characterized by uncontrolled proliferation or/and blockage of differentiation of myeloid progenitor cells. Although a substantial number of gene alterations have been identified, the mechanism by which these abnormalities interact has yet to be elucidated. Over the past decades, zebrafish have become an important model organism, especially in biomedical research. Several zebrafish models have been developed to recapitulate the characteristics of specific myeloid malignancies that provide novel insight into the pathogenesis of these diseases and allow the evaluation of novel small molecule drugs. This report will focus on illustrative examples of applications of zebrafish models, including transgenesis, zebrafish xenograft models, and cell transplantation approaches, to the study of human myeloid malignancies.